2020
DOI: 10.5433/1679-0359.2020v41n1p307
|View full text |Cite
|
Sign up to set email alerts
|

Choline and digestible methionine + cystine supplementation for quail in the laying phase

Abstract: The aim of this study was to evaluate the effect of levels of choline and digestible methionine + cystine in diets for quail in the laying phase. A total of 280 Japanese laying quail were assigned to one of eight treatments in a completely randomized design in a 4 × 2 factorial arrangement consisting of dietary supplementation with four levels of choline (0.0, 0.042, 0.084 and 0.126%) and two levels of digestible methionine + cystine (0.857 and 0.685%), with five replicates and seven birds per plot. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Variations in the energy, protein, and fat content of the feed could affect egg production. Conversely, Griep Junior et al [ 18 ] reported that the administration of choline at levels up to 1260 mg/kg to laying quails improved feed efficiency without changing feed intake or egg production. Khairani et al [ 12 ] revealed that the addition of 1500 mg/kg choline to low methionine quail diets had a positive impact to enhance egg production and egg weight, but had no effect on feed intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variations in the energy, protein, and fat content of the feed could affect egg production. Conversely, Griep Junior et al [ 18 ] reported that the administration of choline at levels up to 1260 mg/kg to laying quails improved feed efficiency without changing feed intake or egg production. Khairani et al [ 12 ] revealed that the addition of 1500 mg/kg choline to low methionine quail diets had a positive impact to enhance egg production and egg weight, but had no effect on feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Another researcher [ 31 ] expressed that the supplementation of choline at levels up to 1260 mg/kg to laying hens did not affect egg quality, except for eggshell breaking strength. Griep Junior et al [ 18 ] reported that the maximum eggshell weight in quails was obtained with the addition of 840 mg/kg choline to the diet, but this effect was not observed for the Haugh unit. Zhai et al [ 33 ] found that the choline level of the diet improved albumen and yolk color score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation